Peran Halaqah Arabiyah Dalam Meningkatkan Keterampilan Membaca Bahasa Arab Terhadap Mahasiswa Program Studi Pendidikan Bahasa Arab Angkatan 2020 Universitas Islam Negerin Datokarama Palu - Wizrah; Didin Faqihudin; Atna Akhiryani (Albariq: Jurnal Pendidikan Bahasa Arab, 2023)
This study discusses "The Role of Halaqah Arabiyah in Improving Arabic Reading of Arabic Language Education Study Program Students class of 2020 Datokarama State Islamic University (UIN) Palu" with the formulation of the problem, namely: 1) How are Halaqah Arabiyah activities carried out by the Arabic Language Education Student Association in Datokarama State Islamic University (UIN) Palu?. 2) What is the role of halaqah Arabiyah in Improving Arabic Reading Skills for Students of the Arabic Language Education Study Program class of 2020 Datokarama State Islamic University (UIN) Palu? This study uses a qualitative method. Data collection techniques were carried out by observation, interviews and documentation. Data analysis techniques and checking the validity of the data. The results showed that the role of the Halaqah Arabiyah State Islamic University (UIN) Datokarama Palu, was enough to improve Arabic reading skills. Halaqah Arabiyah also has a positive influence on the learning achievement of students of the Arabic Language Education Study Program class of 2020.